Evaluating the Heritage Value of the Huluga Archaeological Site - Hernandez, Vito; Faylona, Pamela (Hukay; Vol 9 (2006), 2016)
The heritage value of the Huluga archaeological site is evaluated. A dispute involving issues of site preservation and infrastructure development calls for a rationale to show the heritage value of the site if the place is to be maintained. National cultural properties laws and international herii:age charters are the frameworks for evaluation. Results of archaeological investigations made in the area have been incongruent with what is being told in history and folklore, and this has resulted in debates regarding the national heritage value of Huluga. Our evaluation shows that its heritage value may be more apparent in the regional and international level.